Estudo das propriedades estruturais e dielétricas da matriz cerâmica BaBiTi4O15 com adições de MgO - Gozzo, Cipriano Benedito (2016)
The ceramic BaBi4Ti4O15 (BBT) has been widely studied due to its high dielectric permittivity and its potential application in the radiofrequency and microwave. With the addition of ionic substituents such has improved dielectric properties of the matrix. The present work studies the addition of MgO in the matrix to observe the effects on structural and dielectric properties. The synthesis was carried by the conventional solid state reaction, using a homogenization for 6 hours and temperatures of 850 to 950 ° C for calcining and sintering steps, respectively. It was used amounts of 1, 2 and 5% (w/w) of MgO. Structural characterization techniques were used as x-ray diffraction (XRD) and Raman spectroscopy, density analysis technique by pycnometry, microstructural study by scanning electron microscopy (SEM), study of the dielectric properties in the area of radio frequency and microwaves, respectively, by impedance spectroscopy and Hakki - Coleman techniques. The XRD patterns showed the formation of a single phase to BBT and with 1% of MgO, with 2 and 5% was found a secondary phase Ba0,93(Ti0,79Mg0,21)O2,97. It was observed an increase in the density of the ceramic with the addition of oxide. The SEM showed a decrease in pore size and holes with increased concentration of MgO. The sample with 2% MgO showed a smaller loss value (1,59x10-2 ) and a high dielectric permittivity (70,10) at room temperature at a frequency xix of 1 kHz. The real and imaginary impedance show temperature dependence and frequency. The values decreased with the concentration of MgO in the matrix and there was also an increase in the temperature of the ferroelectric to paraelectric transition. The sample with 1% showed a smaller loss and 2% showed a smaller temperature coefficient of resonant frequency in the microwave region. All samples showed potential for application as dielectric resonator antenna (DRA).